Biotic countermeasures that rescue Nannochloropsis gaditana from a Bacillus safensis infection - Humphrey, Brittany; Mackenzie, Morgan; Lobitz, Mia; Schambach, Jenna Y.; Lasley, Greyson; Kolker, Stephanie; Ricken, Bryce; Bennett, Haley; Williams, Kelly P.; Smallwood, Chuck R.; Cahill, Jesse (Frontiers in Microbiology, 2023)
The natural assemblage of a symbiotic bacterial microbiome (bacteriome) to microalgae in marine ecosystems is now being investigated as a means to increase algal productivity for industry. When algae are grown in open pond settings, biological contamination causes an estimated 30% loss of algal crop. Therefore, new crop protection strategies that do not disrupt the native algal bacteriome are needed to produce reliable, high-yield algal biomass. Bacteriophages offer an unexplored solution to treat pathogenicity of algae because they can eliminate a single species without affecting the bacteriome. To address this, we identified a highly virulent pathogen of the microalga Nannochloropsis gaditana, the bacterium Bacillus safensis, and demonstrated rescue of the microalgae from the pathogen using phage. 16S rRNA amplicon sequencing showed phage treatment did not alter the composition of the bacteriome. It is widely suspected that the algal bacteriome could play a protective role against bacterial pathogens. To test this, we compared the susceptibility of a bacteriome-attenuated N. gaditana culture challenged with B. safensis to a N. gaditana culture carrying a growth-promoting bacteriome. We showed that the loss of the bacteriome increased the susceptibility of N. gaditana to the pathogen. Transplanting the microalgal bacteriome to the bacteriome-attenuated culture reconstituted the protective effect of the bacteriome. Lastly, the success of phage treatment was dependent on the presence of the beneficial bacteriome. This work introduces two synergistic countermeasures against algal pathogenicity and a tractable model for studying interactions between microalgae, phage, pathogens, and the algae microbiome.